The Role of City Spatial Plan (RTRW) on Regional Development in Depok City (West Java Province) - Fikhi Luthfiah; Guswandi Guswandi; Hayuning Anggrahita (Indonesian Journal of Geography, 2023)
Depok City has a role as one of the buffer cities in the Jakarta Metropolitan Area (JMA). Therefore, it has been projected as a residential area and inter-city connection. The latter encourages development resulting in land conversion. If land conversion occurs uncontrollably, it will pose an environmental threat and affect the economic and social conditions, such as decreasing food security capacity and augmenting exclusion and marginalization of the urban poor. Depok City Government has stipulated local regulation on the City Spatial Plan (RTRW), which controls land resource allocation and reference for spatial planning and regional development to integrate and guide all activities related to development. Therefore, this study aims to analyze the development level in Depok City and the impact of RTRW on the development level in Depok City. This study uses a composite index to determine the regional development level and a chi-square test to see the correlation between RTRW regulation and regional development level. Depok City is developing to the north, south, and southeast. RTRW has encouraged regional development in Depok City, although there exist disparities in development levels throughout the region.